The Inhibitory Activity Test of Green Tea Ethanol Extract (Camellia sinensis) Sidamanik Against Escherichia coli - Aliyah Fahmi; Sumaryati Syukur; Zulkarnain Khaidir (Science Midwifery, 2022)
A study was done in analyzing the inhibitory activity of green tea ethanol extracts against Escherichia coli. The green tea is sourced from a tea plantation in Sidamanik, North Sumatra. The green tea was macerated with ethanol 96 % for 24 hours. After that, the filtrate was taken and then concentrated to give a concentrated extract and evaporated ethanol content until run out and obtained thick extract. The thick extract was then diluted with distilled water to extract 5%, 10%, and 15% concentration variations. The test method for inhibitory activity was the disc method using distilled water as a negative blank. The results obtained with blank, 5%, 10% and 15% green tea were 0. 5.7; 7.10, and 8.05 mm The conclusion of this study is that the concentration of the extract is directly proportional to its inhibitory power, and can be used as an antibacterial agent against E. coli.